The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/jocd.14051
|View full text |Cite
|
Sign up to set email alerts
|

Tremellafuciformis polysaccharides inhibit UVA‐induced photodamage of human dermal fibroblast cells by activating up‐regulating Nrf2/Keap1 pathways

Abstract: It is well known that exposure to sunlight is the main cause of oxidative stress in human dermal fibroblasts cells. UVA radiation (320-400 nm) can increase the production of reactive oxygen species (ROS) in cells. By reducing the content of ROS, some active enzyme substances with various antioxidant effects can affect oxidative stress. 1 The enzyme antioxidant system mainly includes superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Cell experiments have showed that NPs from fungi could regulate Nrf2 antioxidant pathway for liver protection ( 192 ), lung protection ( 33 , 105 ), cardioprotection ( 193 ), gastrointestinal protection ( 113 ), anti-oxidation ( 194 , 195 ), anti-aging ( 108 , 196 , 197 ), anti-diabetic ( 102 , 198 ), anti-cancer ( 199 ), and anti-atherosclerosis ( 29 ). Antrodia camphorate polysaccharide exhibited liver protection on LPS-induced Kupffer cells by increasing protein expressions of Keap1, Nrf2, and γ-GCS ( 192 ).…”
Section: Regulation Of Nps On Nrf2 Antioxidant Pathway For Health-pro...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cell experiments have showed that NPs from fungi could regulate Nrf2 antioxidant pathway for liver protection ( 192 ), lung protection ( 33 , 105 ), cardioprotection ( 193 ), gastrointestinal protection ( 113 ), anti-oxidation ( 194 , 195 ), anti-aging ( 108 , 196 , 197 ), anti-diabetic ( 102 , 198 ), anti-cancer ( 199 ), and anti-atherosclerosis ( 29 ). Antrodia camphorate polysaccharide exhibited liver protection on LPS-induced Kupffer cells by increasing protein expressions of Keap1, Nrf2, and γ-GCS ( 192 ).…”
Section: Regulation Of Nps On Nrf2 Antioxidant Pathway For Health-pro...mentioning
confidence: 99%
“…NPs from fungi had anti-oxidation activity on H 2 O 2 -induced HSFs ( 194 ) and LPS-induced RAW264.7 cells ( 195 ) through augmenting protein and/or mRNA expressions of Nrf2, Gstm1, Gstt1, GCLC, GCLM, HO-1, and NQO1, and reducing Keap1 mRNA expression. Those from fungi displayed anti-aging effect against L-Glu-induced HT22 cells ( 108 , 196 ) and UVA-induced HDF cells ( 197 ) via aggrandizing protein and/or mRNA expressions of nuclear Nrf2, Nrf2, SOD1, HO-1, NQO1, and GCLC, and lowering protein and/or mRNA expressions of Keap1 and cytosol Nrf2. Lentinus edodes mycelium polysaccharide had anti-diabetic action against high glucose-induced MIN6 or INS-1 cells, which was related to increment of nuclear Nrf2 protein expression ( 102 , 198 ).…”
Section: Regulation Of Nps On Nrf2 Antioxidant Pathway For Health-pro...mentioning
confidence: 99%
“…Talking about diabetes, people are no strangers to it. In the last century, it was relatively rare for people to get diabetes around the age of 40, however, nowadays, diabetes is getting younger and younger in China; the prevalence of type II diabetes has reached 2% among people aged 8-29 and 6.3% among people aged 30-39, and according to research surveys, the number of people with diabetes in China has exceeded 100 million, ranking first in the world (Fu et al, 2021;Y. Zheng et al, 2019).…”
Section: Hypoglycemicmentioning
confidence: 99%
“…Of course, not away from electronic products can avoid being radiation, in nature, ultraviolet radiation will also affect humans, in some tropical and subtropical areas, due to the strong sunlight, people are subject to strong ultraviolet radiation, which will also be easy to cause skin damage, so in the strong ultraviolet environment should also be done to protect the skin. Fu et al (2021) found that pretreatment with White jellyfungus polysaccharide reduced oxidative stress in UVA‐irradiated human dermal fibroblasts after the pretreatment resulted in a significant reduction in intracellular ROS content, as well as a significant increase in the content of type I collagen, elastin, and hyaluronic acid in skin fibroblasts, which could be added to cosmetics as an effective ingredient for sun protection.…”
Section: Activitymentioning
confidence: 99%
See 1 more Smart Citation